Internalisasi Nilai-Nilai PAI dalam Membangun Kesadaran Lingkungan: Analisis Modal Sosial - azki ulima nur sani azki; Muh. Hanif; Gunbay (Muaddib: Jurnal Pendidikan Agama Islam, 2026)
Students' environmental awareness in schools that have implemented the Adiwiyata program still faces challenges, especially in the aspect of consistency in daily ecological behavior. The values ​​of Islamic Religious Education (PAI) actually have a strong ecological foundation through the concepts of khalifah, amanah, and thaharah, but their internalization in student behavior has not been optimal. This study aims to: (1) describe the process of internalization of PAI values ​​in building environmental awareness in SMP Negeri 2 Purwokerto; (2) analyze the role of social capital in the formation of a culture of environmental care; and (3) explain the supporting factors and obstacles to the internalization of environmental-based PAI values. The study used a qualitative approach with a case study type. Data were obtained through participatory observation, semi-structured interviews with PAI teachers and 9C class students, and documentation of the school's environmental program. Data analysis was carried out through data condensation, data presentation, and thematic conclusion drawing with triangulation of sources and techniques. The results of the study indicate that the values ​​of thaharah and khalifah fil ardh have become the basis for the formation of an environmental care culture. Bonding social capital is evident through teacher role models and the on-duty system; linking social capital is evident through inter-institutional Adiwiyata collaboration; while bridging social capital involving parents has not yet functioned optimally. This research shows that the success of Islamic Religious Education-based environmental education depends not only on the learning materials but also on social relations, role models, and a school culture that are built sustainably.